2012
DOI: 10.1371/journal.pone.0045738
|View full text |Cite
|
Sign up to set email alerts
|

Cardiopulmonary Bypass during Cardiac Surgery Modulates Systemic Inflammation by Affecting Different Steps of the Leukocyte Recruitment Cascade

Abstract: BackgroundIt is known that the use of a cardiopulmonary bypass (CPB) during cardiac surgery leads to leukocyte activation and may, among other causes, induce organ dysfunction due to increased leukocyte recruitment into different organs. Leukocyte extravasation occurs in a cascade-like fashion, including capturing, rolling, adhesion, and transmigration. However, the molecular mechanisms of increased leukocyte recruitment caused by CPB are not known. This clinical study was undertaken in order to investigate wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 79 publications
(100 reference statements)
4
47
0
2
Order By: Relevance
“…Overall, MIrAVR appears to have comparable complication rates and length of stay compared with CrAVR, lending support to its role as a safe alternative to median sternotomy for reoperative AVR. The procedural duration of AVR is of great clinical interest, as prolonged cross-clamp and CPB durations have been shown to be associated with inflammation and poorer surgical outcomes (22,23). In the present study, the cross-clamp and CPB durations were similar between minimally invasive and conventional sternotomy cohorts for rAVR.…”
Section: Discussionsupporting
confidence: 51%
“…Overall, MIrAVR appears to have comparable complication rates and length of stay compared with CrAVR, lending support to its role as a safe alternative to median sternotomy for reoperative AVR. The procedural duration of AVR is of great clinical interest, as prolonged cross-clamp and CPB durations have been shown to be associated with inflammation and poorer surgical outcomes (22,23). In the present study, the cross-clamp and CPB durations were similar between minimally invasive and conventional sternotomy cohorts for rAVR.…”
Section: Discussionsupporting
confidence: 51%
“…An alternative explanation, though, is that serum cystatin C levels were raised via increased production through some mechanism induced by cardiac surgery and CPB (e.g. acute inflammation [31]), hence leading to a false-positive diagnosis of AKI. It is thus possible that the faster rise in serum cystatin C compared to serum creatinine during AKI in some studies [23] is due to the fact that the level of the former is also affected by ancillary processes that occur in parallel with the acute decline in GFR, such as inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study demonstrated that cardiac surgery with CPB abrogates selectin-induced slow leucocyte rolling on E-selectin/ICAM-1 and P-selectin/ICAM-1 [46]. By contrast, chemokineinduced arrest and transmigration was significantly increased.…”
Section: Ec Activates Leucocytesmentioning
confidence: 98%